Distributional Effects of Welfare Reform for Young Adults: An Unconditional Quantile Regression Approach - Øystein Hernaes (Institute of Labor Economics (IZA), 2018)
The paper evaluates the distributional effects on earnings and income of requiring young welfare recipients to fulfill conditions related to work and activation. It exploits within-social insurance office variation in policy arising from a geographically staggered reform in Norway. The reform reduced welfare uptake and for women had large, positive effects in the lower part of the earnings distribution. The effect on the distribution of total income is also positive, thus gains in earnings more than offset reduced welfare benefits. Fewer welfare payments and smaller caseloads make the policy highly cost-effective.
Keywords: C21; D31; H55; I38; J18; J22; 330; social assistance; activation; conditionality; welfare reform; labor supply; quantile treatment effects